2020
DOI: 10.1177/1010539520962940
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Distribution of COVID-19 in Indonesia: A Spatial Analysis

Abstract: The COVID-19 pandemic in Indonesia started with 2 cases on March 2, 2020, and as of May 11, a total of 14 265 people were infected. The government through Task Force for COVID-19 Rapid Response informs the progress of COVID-19 pandemic in Indonesia, but no one has provided a picture of the risk distribution in all provinces in Indonesia. This research is intended to identify high-risk provinces based on risk factors in each province and to find COVID-19 hotspots. This is an ecological study that used aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 6 publications
1
26
1
3
Order By: Relevance
“…It can be seen that provinces in Java Island were clustered in Quandrant 1, which consisted of provinces with a high cumulative number of COVID-19 cases followed by high risk from the surrounding areas. This finding was different from the previous research which illustrated the situation on April 29 th , 2020 where the high-risked provinces were West Java, Jakarta Special Capital Region, Gorontalo, and South Sulawesi (11) . The density of the population and high mobility allowed COVID-19 to spread quickly.…”
Section: Figure 1 Moran's Scatterplot For the Cumulative Number Of Confirmed Covid-19-19 Cases In Indonesia Oncontrasting
confidence: 99%
See 1 more Smart Citation
“…It can be seen that provinces in Java Island were clustered in Quandrant 1, which consisted of provinces with a high cumulative number of COVID-19 cases followed by high risk from the surrounding areas. This finding was different from the previous research which illustrated the situation on April 29 th , 2020 where the high-risked provinces were West Java, Jakarta Special Capital Region, Gorontalo, and South Sulawesi (11) . The density of the population and high mobility allowed COVID-19 to spread quickly.…”
Section: Figure 1 Moran's Scatterplot For the Cumulative Number Of Confirmed Covid-19-19 Cases In Indonesia Oncontrasting
confidence: 99%
“…Several studies about the distribution of COVID-19 also utilizing spatial autocorrelation. Research on the spatial modeling of COVID-19 had been carried out in Yogyakarta, Indonesia (10) , and the spread of COVID-19 in Indonesia in April 2020 (11) . Research on the distribution of COVID-19 with spatial statistics has also been carried out in several other countries, including China (12) , Kuwait (13) , South Korea (14) , Bangladesh (15) .…”
Section: Introductionmentioning
confidence: 99%
“…Spatial statistics and the modeling tool of ArcGIS 10.6 were used to test whether the confirmed provincial and municipal cases had significant global or local spatial autocorrelation. Spatial autocorrelation, which measures spatial autocorrelation based on feature locations and eigenvalues, can be divided into global spatial autocorrelation and local spatial autocorrelation ( Eryando et al, 2020 ). Use global Moran's I statistics to assess whether the cumulative number of confirmed COVID-19 cases in each region is spatially relevant.…”
Section: Methodsmentioning
confidence: 99%
“…Eventually, there would be more person-to-person contact, leading to human-to-human transmission. 19 Several studies have suggested the common role of family clusters in developing the ongoing epidemic. A recent study in the UK estimated that contact within households was responsible for roughly 70% of SARS-CoV-2 transmission when widespread community control measures were in place.…”
Section: Discussionmentioning
confidence: 99%